Design, Production, and Performance Assessment of a Remote Monitored Automated Solar Powered Egg Incubator - Malembeka, Marvin; Kanyanga, Prof Shamitiba. B. (American Journal of Computing and Engineering, 2025)
Purpose: The research aimed to create an automated solar-powered egg incubator using locally available materials that can be remotely monitored and improve Zambia's poultry farming industry. Materials and Methods: The design model was created using Solidworks, and the simulation was done using Ansys, MATLAB, and Proteus. The incubator was equipped with a DHT22 sensor to measure temperature and humidity, GSM-GPRS Sim 800 and Blynk IoT Cloud for remote monitoring, two Nano-Arduino for processing, and a solenoid valve for auto-refilling the water in the incubator. Limit switches also positioned the egg setter, ensuring the incubator door was airtight. Findings: The operation and performance of a solar-powered, remote-monitored poultry incubator using the Blynk IoT cloud platform. The system enables real-time monitoring and control of critical parameters such as temperature, humidity, water level, egg turning, and door state. Data is visualized through the Blynk dashboard, including graphs and gauges accessible remotely. The incubator consistently maintained optimal hatching conditions, with alerts and automated responses triggered when parameters deviated from preset thresholds such as activating the water valve when water levels dropped. Reports generated by Blynk allow for effective performance assessment and troubleshooting, isolating issues related to either the incubator environment or egg fertility. Temperature and humidity readings occasionally skip data rows due to sensor sampling intervals, but overall, the system provides timely and accurate updates.Tests were conducted, and the incubator maintained a steady temperature and humidity of 37°C and 65% for chicken eggs, respectively. Despite being switched off for 5 hours, the incubator temperature remained stable, and its energy efficiency was attributed to the proper selection of fabrication materials. Unique Contribution to Theory, Practice and Policy: This innovation has the potential to significantly improve the poultry industry in Zambia, especially in areas without access to grid power supply. Farmers can benefit from affordable and economically viable incubators with advanced managerial technologies despite their absence to directly manage the hatching process. The continent's abundant solar resources can solve farmers' challenges of low access rates and unreliable power supply and increase the marginal revenue from hatcheries.